RELIGIOUS IDENTITY TRANSFORMATION: Cultural Interbreeding Between Dayak Indigenous Culture and Islam (State Islamic University (UIN) of Sunan Ampel Surabaya, 2021)
The arrival of imported religions, Islam and Chistianity in particular, in West Kalimantan creates cultural dialectic and transformation within local indigenous Dayak’s culture and belief. This article tries to explore on cultural interbreeding between Dayak indigenous culture and Islam in West Kalimantan, Indonesia. The findings have revealed that the interaction between local Dayak culture with variant of Islam creates new cultural identity such as Senganan Dayak in Semabi. This new identity is the consequence for those who convert to Islam as they do not abandon the Dayak identity. However, the massive conversion of Dayak to Islam does not necessarily imply the downgrading of identity from Dayak to Malay; instead they still remain to be Dayak in spite of their conversion to new religion. Another transformation occurred within tradition such as the ritual of “ngantar buah pulang (bring fruit home)”. This Dayak indigenous ritual is replaced with Islamic kind of thanksgiving ritual and replaces the spelling of magic spell with supplication to God Almighty.